2016
DOI: 10.1111/modl.12310
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Language Learners: Socioinstitutional Mechanisms and their Consequences

Abstract: Through examination of one recently manufactured term for language learners (Long‐term English Learners) and review of a century of MLJ articles, we examine varying ‘socioinstitutional’ conceptualizations of second/foreign/heritage language learners as shaped by educational institutions and related stakeholders over time, given evolving understandings of the practice of language teaching that are directly related to theoretical, political, and institutional discourses. We focus very specifically on constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 189 publications
(223 reference statements)
0
53
0
2
Order By: Relevance
“…In a more salutary light, the compression of time and space that technology affords, the opportunities for international travel and careers in a global society, and the chances for ordinary citizens to lead transnational lives have made the advantages of knowing another language more apparent. Given the polarity of the zeitgeist, amidst “the increasing complexities of language use in a global society … it is clear that simple answers to the question, ‘how does one teach language?’ (or ‘who are learners?’) will not be forthcoming” (Kibler & Valdés, , p. 110). It is equally obvious that seeking answers in SLA research amidst such complexity will require a new mode of thinking.…”
Section: The Zeitgeistmentioning
confidence: 99%
“…In a more salutary light, the compression of time and space that technology affords, the opportunities for international travel and careers in a global society, and the chances for ordinary citizens to lead transnational lives have made the advantages of knowing another language more apparent. Given the polarity of the zeitgeist, amidst “the increasing complexities of language use in a global society … it is clear that simple answers to the question, ‘how does one teach language?’ (or ‘who are learners?’) will not be forthcoming” (Kibler & Valdés, , p. 110). It is equally obvious that seeking answers in SLA research amidst such complexity will require a new mode of thinking.…”
Section: The Zeitgeistmentioning
confidence: 99%
“…It also includes students who should be labeled as ELs, but are not because they were not flagged on a home language survey or because of an overly generous scoring on an ELP screener. These students may not receive services appropriate to their linguistic needs because of the way they were initially labeled (Cimpian et al, 2017;Kibler & Valdés, 2016).…”
Section: The Fluid Viewpointmentioning
confidence: 99%
“…Another issue from the fluid viewpoint is that EL classification can be a stigmatizing label for students from minoritized language backgrounds close to proficiency (Dabach, 2014;Umansky, 2016). Kibler and Valdés (2016) conducted a historical review of the conceptualization of long-term ELs in which they deconstructed the sequential progression assumed in EL classification. In doing so, these authors argued that the EL label can do more harm than good for students identified as long-term ELs.…”
Section: The Fluid Viewpointmentioning
confidence: 99%
“…The article concludes with the identification of some aspects of FL classrooms that merit research attention as the MLJ moves into its second century. A number of additional central issues related to the FL classroom receive detailed treatment in other contributions to this volume, notably the roles of teachers (Kubanyiova & Crookes, 2016); applications of technology within and beyond the classroom walls (Chun, Smith, & Kern, 2016); and socioinstitutional perspectives on classroom learners (Kibler & Valdés, 2016).…”
mentioning
confidence: 99%